EVIDANCE BASED CASE REPORT (EBCR) : PENGARUH KOMPRES AIR HANGAT TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: One of the natural processes that will be experienced by pregnant women is childbirth. This process will cause stretching and dilation of the cervix due to contractions of the uterine muscles to push the baby out. Pregnant women will feel pain or labor pain during the first active phase, because the uterus contracts more and more frequently to expel the products of conception. Therefore, most mothers experience pain during childbirth, but the intensity of pain that is felt will be different for each woman giving birth. This is often influenced by the mother's psychology during childbirth, namely fear and effort against labor and support from those closest to her during the birth process. Efforts that can be made to reduce labor pain can be pharmacological and non-pharmacological, such as warm water compresses. Purpose: of this report is to find out whether warm water compresses can reduce labor pain in the first stage of labour. Method: evidance based cased report (EBCR) search for article uses the Pubmed and Google Schoolar databases. Intervention is carried out by applying warm water compresses to the mother for 20 minutes, repeated every 1 hour until complete dissection. Result: from the assessment of the mother's perceived pain using the Visual Analogue Scale (VAS) before and after the intervention showed a significant difference with the previous decrease in severe pain to moderate pain. Conclusion: Warm water compresses are effective in reducing labor pain in the first stage